Soil chemical properties affected by cover crops under no-tillage system - NASCENTE, ADRIANO STEPHAN (Revista Ceres, 2015)
The use of cover crops in no-tillage systems (NTS) can significantly improve the soil’s fertility. Thus, a study was performed to evaluate changes in chemical properties of soil caused by cover crops in a no-tillage system. The field experiment consisted of the following crop rotation: cover crops/rice/cover crops/rice. The experimental design was in randomized blocks with three replications. Treatments consisted of four cover crops (Brachiaria brizantha (Hochst. ex A. Rich.) Stapf. cv. Marandu, Brachiaria ruziziensis R. Germ. and C.M. Evrard, Panicum maximum Jacq. cv. Colonião, and Pennisetum glaucum (L.) R. Br. cv. BN-2) and fallow (control treatment). Soil samples were collected at the beginning of the summer crop in Oct 2007, Oct 2008 and Oct 2009 at 0-5 cm soil depth. The use of cover crops provided for a significant increase in the level of nutrients, soil organic matter, cation exchange capacity, and base saturation in the soil. Soil fertility improved from the first to second year with the growing of cover crops. The soil under cover crops P. glaucum, B. ruziziensis, and B. brizantha showed higher fertility than the area under fallow.